Awareness of movement does not facilitate robot-assisted passive motor learning. (17th January 2017) - Sakamoto, Takashi; Kondo, Toshiyuki
Graphical Abstract: Abstract : Robot-assisted therapy is a promising approach for stroke rehabilitation. However, the rational basis of robot-assisted motor learning and effective training strategies remain unclear due to several factors, such as use-dependent plasticity, active motor intent, awareness of movement and sensory anticipation, positive sensory feedback, and participant individuality. Among these factors, our research focuses on the role of awareness in robot-assisted passive motor learning. In the study, we hypothesize that awareness of task goal and initiation timing of movement improves sensory anticipation and thus facilitates motor adaptation even during passive motor learning. Our experimental results suggest that awareness of movement does not have a positive effect on robot-assisted passive motor learning.